FAKTOR DOMINAN YANG BERHUBUNGAN DENGAN PERILAKU PEMERIKSAAN PAP SMEAR PADA WANITA USIA SUBUR - Salmah Salmah; Wahyudin Rajab; Eha Djulaeha (Jurnal Ilmu dan Teknologi Kesehatan, 2013)
Cancer of Serviks is the deadly disease that has an effect in the woman healthy on the world and the first rank in the cancer case that attack the woman. In Asia, there is 266.000 new case of cancer of serviks that is diagnosed every year(Singso,2006). Meanwhile, the death caused by estimated reached 233.400 cases every year (WHO.2002). The right Medical treatment will help to stop the abnormal cells of the cancer of serviks that can be detected with a test called " Pap Smear". We can enabling some medical act, before the cells developed to be cancer's cell. This observation using crossectional study, population in the WUS' observation that has the majority in Graha Prima complex and chosen as the sample with randomly. The goal of this observation is to get information about behavior of the checking with PAP Smear to WUS. The result of the observation that show there is a relation between checking with Pap Smear to WUS : Income, Knowledge, attitude, social support, the dominant Factors is Social Support, having OR 13,63 (95%, CI : 2,60 71,46) Conclution social support is the biggest variable that related with checking Pap Smear to WUS' behavior.